Slope Stability Analysis of East Ring Road Construction at Sadawarna Dam With Shear Strength Reduction Method - Putra, Rafino Kurnia; Zakaria, Zufialdi; Alfadli, Muhammad Kurniawan; Sophian, Raden Irvan; Khoirullah, Nur; Firmansyah, Yusi (Journal of Geological Sciences and Applied Geology, 2023)
Slope stability has been a problem that studied on geotechnical works for the uncertainties such as varieties of soil behaviours to unpredicted failure of measurements and samplings. The Limit Equilibrium Method (LEM) has been popular for decades for its convenience but cannot determine displacement thus the result could be uncertain. As computational calculations have been developed, the Finite Element Method (FEM) began to use as a tool to not only determine factor of safety, but also determine displacement and forces that affect slope’s stability. This research was done to analysed slope stability using Shear Strength Reduction (SSR) and compared it to general method such as Limit Equilibrium Method (LEM). The research was conducted on a section in Sadawarna DAM ring road area, Subang, West Java. Slope on research area was divided into two layers with the bottom layer relatively non-cohesive compared to the top of layer. Both soil however dominantly consist with fine grain soil such as silt and clay. The upper layer of slope can contain more water with liquid limit of 73,46% compared to the lower layer with 68,27% liquid limit.  Simulation result showed slope that analysed using SSR method has Factor of Safety (FoS) 0,12 lower than LEM method. SSR method could be used to analysed pessimistic value at worst scenario and could predicted deformation of slope.